EXTENSIVE READING OF TENTH GRADERS: IN RELATION TO CRITICAL THINKING (RETAIN, 2020)
Abstract Extensive reading was reading of a large number of texts or materials outside classroom and also for general comprehension with intention of getting pleasure from the text that is crucial for acquisition. While critical thinking was the ability to think rationally and clearly, understanding the logical connection between ideas. This study was conducted to find out how the students’ extensive reading, how the students’ critical thinking and whether any relation between the students’ extensive reading and their critical thinking. The results from the students’ extensive reading indicated that the students still have good interest and motivation toward extensive reading. While the results of students’ critical thinking test were low. That indicated there must be a cause. It might be the students mental hectic which were caused a lot of numbers of questions that had to be done in limited time and also it might be the students answered the questions carelessly. Therefore, the result of the correlation between extensive reading and critical thinking was not significant, it concluded that there was no correlation between both of them. Keywords: Extensive Reading, Critical Thinking